Focal Therapy in the Management of Prostate Cancer: An Emerging Approach for Localized Prostate Cancer - Nomura, Takeo (Hindawi Publishing Corporation, 2012)
A widespread screening with prostate-specific antigen (PSA) has led increased diagnosis of localized prostate cancer along with a reduction in the proportion of advanced-stage disease at diagnosis. Over the past decade, interest in focal therapy as a less morbid option for the treatment of localized low-risk prostate cancer has recently been renewed due to downward stage migration. Focal therapy stands midway between active surveillance and radical treatments, combining minimal morbidity with cancer control. Several techniques of focal therapy have potential for isolated ablation of a tumor focus with sparing of uninvolved surround tissue demonstrating excellent short-term cancer control and a favorable patient's quality of life. However, to date, tissue ablation has mostly used for near-whole prostate gland ablation without taking advantage of accompanying the technological capabilities. The available ablative technologies include cryotherapy, high-intensity focused ultrasound (HIFU), and vascular-targeted photodynamic therapy (VTP). Despite the interest in focal therapy, this technology has not yet been a well-established procedure nor provided sufficient data, because of the lack of randomized trial comparing the efficacy and morbidity of the standard treatment options. In this paper we briefly summarize the recent data regarding focal therapy for prostate cancer and these new therapeutic modalities.